(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The case of funerary epigraphy is paradigmatic to analyse the relationship between the Roman presence in Southern Spain and the appearance of the epigraphic habit. In spite of the tendency to the funerary monumentalization that archaeology has detected from the end of II Punic War, the first epitaphs, in Latin or Iberian language, do not appear until the 1st century and in a very limited number until the time of Augustus. The aim of this paper is to present these initial testimonies, suggesting how both the previous traditions and the new Roman models were used in the elaboration of the first epitaphs in the Southern indigenous areas.